Bibliometric insights into the dynamics of schizophrenia and obesity research - Mat Rasid, Siti Norain; Abd. Rahim, Nour El Huda; Mohamed Bakrim, Norbaiyah; Abdull Jalil, Mohd Asyraf; A.Talib, Norlelawati; Md Rosli, Ahmad Nabil; Wan Salleh, Wan Muhamad Salahudin; Kaderi, Mohd Arifin; Azman, Norainin Sofiya (FACULTY OF MEDICINE AND HEALTH SCIENCES, 2025)
Schizophrenia and obesity are two complicated health disorders that affect both individuals and society. Comprehensive research that investigates the interplay between these two conditions is required. Therefore, a bibliometric analysis was performed to investigate the landscape of schizophrenia and obesity research. The bibliometric analysis was conducted using the Scopus analyser and VOSviewer software. There have been fluctuations in annual output. De Hert is the most influential contributor in this research field, where medicine dominates as the primary subject area (57.5%). A study on the prevalence of metabolic syndrome among schizophrenia is the most cited article. The studies were carried out by distinct clusters of experts, with the United States being the leading contributor. An analysis of the author's keywords showed five main areas of interest. This bibliometric analysis offers an in-depth review of the knowledge gap in these fields and suggests specific recommendations for future research.